The Synergy of ADAM17-Induced Myocardial Inflammation and Metabolic Lipids Dysregulation During Acute Stress: New Pathophysiologic Insights Into Takotsubo Cardiomyopathy - Adu-Amankwaah, Joseph; Adzika, Gabriel Komla; Adekunle, Adebayo Oluwafemi; Ndzie Noah, Marie Louise; Mprah, Richard; Bushi, Aisha; Akhter, Nazma; Xu, Yaxin; Huang, Fei; Chatambarara, Benard; Sun, Hong (Frontiers in Cardiovascular Medicine, 2021)
Due to its reversible nature, Takotsubo cardiomyopathy (TTC) is considered an intriguing and fascinating cardiovascular disease characterized by a transient wall motion abnormality of the left ventricle, affecting more than one coronary artery territory, often in a circumferential apical distribution. TTC was discovered by a Japanese cardiovascular expert and classified as acquired primary cardiomyopathy by the American Heart Association in 1990 and 2006, respectively. Regardless of the extensive research efforts, its pathophysiology is still unclear; therefore, there are no well-established guidelines specifically for treating and managing TTC patients. Increasing evidence suggests that sympatho-adrenergic stimulation is strongly associated with the pathogenesis of this disease. Under acute stressful conditions, the hyperstimulation of beta-adrenergic receptors (β-ARs) resulting from excessive release of catecholamines induces intracellular kinases capable of phosphorylating and activating A Disintegrin and Metalloprotease 17 (ADAM17), a type-I transmembrane protease that plays a central role in acute myocardial inflammation and metabolic lipids dysregulation which are the main hallmarks of TTC. However, our understanding of this is limited; hence this concise review provides a comprehensive insight into the key role of ADAM17 in acute myocardial inflammation and metabolic lipids dysregulation during acute stress. Also, how the synergy of ADAM17-induced acute inflammation and lipids dysregulation causes TTC is explained. Finally, potential therapeutic targets for TTC are also discussed.